A discrete-time queueing system with three different strategies - Atencia-McKillop, Iván; Padilla-Domínguez, Yolanda Carmen; Galán-García, José Luis; Aguilera-Venegas, Gabriel; Rodríguez-Cielos, Pedro; Galán-García, María Ángeles (Elsevier, 2021)
We consider a discrete-time Geo/G/1/inf system in which a customer that finishes its first essential service may opt to abandon the system, to receive a second optional service or to go at the head of the queue in order to receive another essential service. We study the Markov chain underlying the considered queueing system and its ergodicity condition. Using a generating function approach the distribution of the number of customers in the queue and in the system as well as their respective means are given. The busy period of an auxiliary system, that will be useful to study of the customers delay, is analysed. The distributions of the sojourn time of a customer in the server, the queue and the system are provided. In order to illustrate the effect of the parameters on several performance characteristics some numerical examples are given. Finally, a section of conclusions commenting the main research contributions of this paper is presented.
Keywords: Sistemas de control por retroalimentación; Feedback; Realimentación; Servicio opcional; Periodo ocupado; Tiempos de estancia